2022
DOI: 10.26650/jecs2021-1056971
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change on Water Resources, Agricultural Production and Food Security: Evidence from Turkiye

Abstract: Since agricultural production depends mainly on nature and uses surface and groundwater reservoirs, changes in existing water resources significantly affect this sector. Again, changes in global climate bring changes in water levels, consequently affecting agriculture, food supply, and income sources of households in different areas. However, to date, no such research has investigated the farmers who are the producers and the most vulnerable group to the impacts of climate change. Therefore, this paper explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Later numerous studies, focused on the impact of climate change on water resources in the future, concluded that under the influence of socio-economic factors, water stress increases and varies from region to region [63][64][65][66][67]. Consequently, changes in water resources significantly affect agriculture through the quality and quantity of yields, causing problems in the supply of food markets and generating economic difficulties [68].…”
Section: Introductionmentioning
confidence: 99%
“…Later numerous studies, focused on the impact of climate change on water resources in the future, concluded that under the influence of socio-economic factors, water stress increases and varies from region to region [63][64][65][66][67]. Consequently, changes in water resources significantly affect agriculture through the quality and quantity of yields, causing problems in the supply of food markets and generating economic difficulties [68].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the farmers will face a food supply crisis for their consumption (Devereux & Edwards, 2004). Moreover, Konya, the leader of Turkey's agriculture sector with its vast flat land, uses primarily surface and groundwater reservoirs (Bayramoğlu & Ağızan, 2022;İslam, 2022a) for a maximum harvest of agricultural products. İn addition, changes in climate characteristics will have negative impacts not only on agricultural production but also on the food supply, health, industry, and tourism industry of the affected area (T.R.…”
Section: Introductionmentioning
confidence: 99%
“…İn addition, environmental pollution and global climate change also affect the basin water, which consequently limits the use of water in the irrigation system for proper agricultural production When the producers cannot invest in new irrigation technology for sufficient agricultural products, some of them migrate to other areas though climate-induced internal migration is not adequately recorded (İslam, 2022b) nor the migrants get their refugee identity (İslam, 2016c). Studies show that since Konya has been experiencing severe drought due to the impacts of climate change on water resources of the area, agricultural production, i.e., production of wheat, barley, etc., has drastically been reduced in the recent years (Al-Bakri et al, 2013;İslam, 2022a;Soylu, 2021;Topak & Acar, 2010). This situation leads to an income crisis for many producers, destabilizing the households' income source and contributing to the region's migration process.…”
Section: Introductionmentioning
confidence: 99%